Access to education: The challenges of school transportation in the rural area of the municipality of Apiacá/ES (Research, Society and Development, 2024)
The study addresses school transportation as a means of access and retention in education in rural areas. The aim was to analyze the quality of school transportation provided by the public entities of Apiacá/ES and its effectiveness in meeting the needs of the local community. This is a descriptive study with a qualitative approach, which used interviews with six participants, document review, and observation in a school unit in the rural area of the municipality. The results show that the conditions of the unpaved roads in the region represent a significant challenge that impacts the quality of school transportation in Apiacá/ES, especially in the Batatal Community. Logistic challenges, related to the efficient management of resources in a municipality of reduced dimensions, influence punctuality and school attendance rates. Given this, the resources of the PNATE become essential in financing and maintaining school transportation in rural areas of small communities.